The paradox of intragroup conflict: A meta-analysis. - de Wit, Frank R. C.; Greer, Lindred L.; Jehn, Karen A. (Journal of Applied Psychology, 2012)
Since the meta-analysis by De Dreu and Weingart (2003b) on the effects of intragroup conflict on group outcomes, more than 80 new empirical studies of conflict have been conducted, often investigating more complex, moderated relationships between conflict and group outcomes, as well as new types of intragroup conflict, such as process conflict. To explore the trends in this new body of literature, we conducted a meta-analysis of 116 empirical studies of intragroup conflict (n = 8,880 groups) and its relationship with group outcomes. To address the heterogeneity across the studies included in the meta-analysis, we also investigated a number of moderating variables. Stable negative relationships were found between relationship and process conflict and group outcomes. In contrast to the results of De Dreu and Weingart, we did not find a strong and negative association between task conflict and group performance. Analyses of main effects as well as moderator analyses revealed a more complex picture. Task conflict and group performance were more positively related among studies where the association between task and relationship conflict was relatively weak, in studies conducted among top management teams rather than non-top management teams, and in studies where performance was measured in terms of financial performance or decision quality rather than overall performance.